Tungsten etching inhibition composition
By using a composition containing corrosion inhibitor and silicate particles during chemical mechanical polishing process to control the pH value, the problem of poor corrosion in the polishing process is solved, and a more stable and efficient polishing effect is achieved.
Patent Information
- Application Number
- JP2022507825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-08
- Filing Date
- 2020-08-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-08-04
AI Technical Summary
The prior art is difficult to effectively suppress etching of tungsten during chemical mechanical polishing, resulting in poor corrosion of tungsten in the grooves and affecting the polishing effect.
A chemical mechanical polishing composition containing corrosion inhibitors such as silicate, sodium hydroxide and sodium sulfate is used, and silicate particles are added as abrasives to the composition, and the pH value of the composition is controlled to be between 5.0 and 11.0.
It significantly reduces the static etching rate of tungsten, effectively suppresses the corrosion of tungsten, improves the stability and efficiency of the polishing process, and maintains the polishing rate.
Smart Images

Figure 0007654635000001 
Figure 0007654635000002
Abstract
Description
[Technical field]
[0001] The presently claimed invention relates to compositions and methods for inhibiting etching. In particular, the presently claimed invention relates to compositions and methods for inhibiting the etching of tungsten. [Background technology]
[0002] background Integrated circuits, which form semiconductor devices, are a collection of active devices that are chemically and physically connected within a substrate and interconnected by multi-level interconnects. Typically, the multi-level interconnects form the functional circuitry and consist of a first metal layer, an interlevel dielectric layer, and an optional third metal layer. As each layer is formed, it is planarized to allow subsequent layers to be formed on top of the newly formed layer. In the semiconductor industry, chemical mechanical polishing (CMP) is a well-known technique that is applied in the manufacture of advanced photonic, microelectromechanical, and microelectronic materials and devices, such as semiconductor wafers.
[0003] CMP utilizes the interplay of chemical and mechanical action to achieve planarity of the surface to be polished. The chemical action is provided by a chemical composition, also called a CMP composition or CMP slurry. The mechanical action is achieved by pressing a polishing pad, usually against the surface to be polished. The pad is attached to a moving platen. In a typical CMP process step, a rotating wafer holder brings the wafer to be polished into contact with the polishing pad. The CMP composition is usually applied between the wafer to be polished and the polishing pad.
[0004] With the continuing shrinkage of feature sizes in ultra-large scale integrated circuit (ULSI) technology, the size of copper interconnect structures is becoming smaller and smaller. To reduce RC delay, which is the delay in signal speed through circuit wiring caused by resistance (R) and capacitance (C), the thickness of the barrier or adhesion layer of copper interconnect structures is being reduced. The traditional copper barrier / adhesion layer stack Ta / TaN is no longer suitable because Ta has a relatively high resistivity and copper cannot be directly electroplated onto Ta. Increasingly, interconnects are being formed using tungsten as the conductive material. A typical manufacturing process uses CMP to reduce the thickness of the tungsten overcoat layer until a flat surface is obtained that exposes the raised portions of silicon dioxide and allows the formation of a dielectric layer. Generally, CMP compositions for polishing tungsten-containing substrates contain compounds capable of etching tungsten. Compounds capable of etching tungsten convert tungsten into a soft oxide film that can be removed by mechanical abrasion. The polishing step of the CMP process removes the tungsten overcoat layer to ensure the planarity of the substrate. However, this process can result in undesirable erosion of the tungsten due to a combination of static etching and the mechanical action of the abrasive.
[0005] Compositions which contain inhibitors for tungsten etching are known in the state of the art and are described, for example, in the following documents:
[0006] US 6,273,786 B1 describes methods and compositions using tungsten corrosion inhibitors to protect tungsten, including phosphates, polyphosphates, and silicates, specifically potassium hypophosphite and potassium silicate.
[0007] US6,083,419 A describes a chemical mechanical polishing composition comprising a compound capable of etching tungsten and at least one tungsten etching inhibitor, which is a compound containing at least one functional group selected from nitrogen-containing heterocycles without nitrogen-hydrogen bonds, sulfides, oxazolidines, or mixed functional groups in one compound.
[0008] US 9,303,188 B2 discloses a chemical mechanical polishing composition containing an amine compound that inhibits the etching of tungsten.
[0009] The methods and compositions disclosed in the prior art have limitations. In the methods and compositions disclosed in the prior art, the inhibitors are not always effective in preventing tungsten erosion in trenches. In addition, the use of high concentrations of inhibitors known in the prior art can unacceptably reduce the polishing rate of a substrate made of a tungsten layer. Therefore, there is a need for improved compositions and methods for inhibiting tungsten etching, as well as compositions that can be realized to reduce tungsten erosion during CMP processes. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] US6,273,786 B1 [Patent Document 2] US6,083,419 A [Patent Document 3] US9,303,188 B2 Summary of the Invention [Problem to be solved by the invention]
[0011] It is therefore an object of the presently claimed invention to provide an improved composition and method for inhibiting the etching of tungsten.
[0012] overview It has been surprisingly found that the compositions of the presently claimed invention reduce the static etch rate for tungsten and are capable of inhibiting the etching of tungsten. [Means for solving the problem]
[0013] Thus, one aspect of the present invention is a composition for inhibiting tungsten etching, comprising: (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; and (C) Aqueous medium Including, Compositions are provided, wherein the pH of the composition is in the range of ≧5.0 to ≦11.0.
[0014] In another aspect, the presently claimed invention comprises chemically mechanically polishing a substrate (S) used in the semiconductor industry in the presence of a composition as described herein, wherein the substrate (S) is (i) tungsten and / or (ii) Tungsten alloys The present invention is directed to a method for manufacturing a semiconductor device (element, apparatus), including the steps of:
[0015] In another aspect, the presently claimed invention is directed to the use of the compositions described herein to inhibit the etching of tungsten.
[0016] The presently claimed invention has at least one of the following advantages: (1) The compositions and methods of the presently claimed invention exhibit improved performance in inhibiting etching, particularly inhibiting tungsten etching. (2) The compositions and methods of the presently claimed invention prevent erosion of tungsten during chemical mechanical polishing of tungsten-containing substrates. (3) The compositions of the presently claimed invention provide stable formulations or dispersions that do not undergo phase separation. (4) The method of the present claimed invention is easy to apply and requires as few steps as possible. (5) The compositions and methods of the presently claimed invention do not affect the polishing rate of a substrate during chemical mechanical polishing.
[0017] Other objects, advantages and uses of the present claimed invention will become apparent to those skilled in the art from the following detailed description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Detailed Description The following detailed description is merely exemplary in nature and is not intended to limit the claimed invention or the application and uses of the claimed invention, nor is it intended to be bound by any theory presented in the preceding technical field, background, brief summary, or the following detailed description.
[0019] As used herein, the terms "comprising," "comprises," and "comprised of" are synonymous with "including," "includes," or "containing," and are inclusive or open-ended and do not exclude additional, unrecited members, elements, or method steps. As used herein, the terms "comprising," "comprises," and "comprised of" are understood to include the terms "consisting of," "consists," and "consists of."
[0020] Additionally, the symbols "(a)", "(b)", "(c)", "(d)", etc., used in the specification and claims are used to distinguish between similar elements and not necessarily to describe a sequence or chronology. It is understood that symbols used in this manner are interchangeable under appropriate circumstances and that the embodiments of the presently claimed invention described herein may be performed in sequences other than those described or illustrated herein. When symbols such as "(A)", "(B)" and "(C)" or "(a)", "(b)", "(c)", "(d)", "(i)", "(ii)" etc., relate to steps of a method or method of use or assay, there is no consistency in time or consistency of time intervals between the steps. That is, unless otherwise stated in the application hereinbefore or below, the steps may be performed simultaneously or there may be time intervals of seconds, minutes, hours, days, weeks, months, or even years between such steps.
[0021] The following sections set forth various aspects of the claimed invention in more detail. Each aspect so defined may be combined with any other aspect or aspects, unless expressly indicated to the contrary. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous.
[0022] Throughout this specification, when "one embodiment" or "embodiment" or "preferred embodiment" is mentioned, it means that the particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the invention described in the claims. Thus, the appearance of the phrase "in one embodiment" or "in an embodiment" or "in a preferred embodiment" in various places throughout this specification does not necessarily refer to the same embodiment, but may. Furthermore, the features, structures, or characteristics may be combined in any suitable manner in one or more embodiments, as would be apparent to one of ordinary skill in the art from this disclosure. Furthermore, although some embodiments described herein include features that are not included in other embodiments, it is meant that combinations of features from different embodiments are within the scope of the present subject matter and form different embodiments. This is understood by one of ordinary skill in the art. For example, in the appended claims, any of the embodiments described in each claim may be used in any combination.
[0023] Furthermore, ranges defined throughout the specification are inclusive, i.e., a range of 1 to 10 means that both values 1 and 10 are included in the range. For the avoidance of doubt, applicants reserve their legal right to claim equivalents pursuant to applicable law.
[0024] In the present invention, the "mass %" used in the present invention is based on the total mass of the coating composition. Furthermore, the mass % of all compounds in each component described below should total 100 mass %.
[0025] For purposes of this claimed invention, a corrosion inhibitor is defined as a chemical that forms a protective molecular layer on the surface of a metal.
[0026] For purposes of this claimed invention, a chelating agent is defined as a chemical that forms a soluble complex molecule with certain metal ions, rendering the ions inactive and unable to react normally with other elements or ions to form precipitates or scale.
[0027] For purposes of the present claimed invention, low-k materials are those with a k value (dielectric constant) less than 3.5, preferably less than 3.0, and more preferably less than 2.7. Ultra-low-k materials are those with a k value (dielectric constant) less than 2.4.
[0028] In the presently claimed invention, colloidal inorganic particles are inorganic particles that can be produced by wet precipitation processes, and fumed inorganic particles are particles that can be produced, for example, by high temperature flame hydrolysis of metal chloride precursors with hydrogen in the presence of oxygen, for example, using the Aerosil® process.
[0029] In the present claimed invention, "colloidal silica" refers to silicon dioxide produced by condensation polymerization of Si(OH)4. The precursor Si(OH)4 can be obtained, for example, by hydrolysis of high purity alkoxysilanes or by acidification of aqueous silicate solutions. Such colloidal silica can be produced according to U.S. Pat. No. 5,230,833. Alternatively, various commercial products can be obtained, such as Fuso® PL-1, PL-2, and PL-3, Nalco 1050, 2327, and 2329, and similar products available from DuPont, Bayer, Applied Research, Nissan Chemical, Nyacol, and Clariant.
[0030] In the present invention, the mean particle size is defined as the d of the particle size distribution of the inorganic abrasive particles (A) in the aqueous medium (H). 50 Define it as a value.
[0031] In the presently claimed invention, the average particle size is measured, for example, by dynamic light scattering (DLS) or static light scattering (SLS). These and other methods are well known in the art. See, for example, Kuntzsch, Timo; Witnik, Ulrike; Hollatz, Michael Stintz; Ripperger, Siegfried; Characterization of Slurries Used in Chemical Mechanical Polishing (CMP) in the Semiconductor Industry; Chem. Eng. Technol; 26 (2003), Vol. 12, p. 1235.
[0032] In the presently claimed invention, dynamic light scattering (DLS) typically uses a Horiba LB-550V (DLS, Dynamic Light Scattering) or other similar instrument. This technique measures the hydrodynamic diameter of a particle as it scatters a laser light source (λ=650 nm) detected at an angle of 90° or 173° to the incident light. The change in intensity of the scattered light, due to random Brownian motion as the particle passes through the incident beam, is monitored as a function of time. The autocorrelation function performed by the instrument as a function of the delay time is used to extract the decay constant. Smaller particles pass through the incident beam at a faster rate, corresponding to faster decay.
[0033] In the presently claimed invention, the damping constant is proportional to the diffusion coefficient Dt of the inorganic abrasive particles and is used to calculate the particle size according to the Stokes-Einstein equation:
[0034]
number
[0035] Here, the suspended particles are assumed to (1) have a spherical morphology and (2) be uniformly dispersed throughout the aqueous medium (i.e., not aggregated). This relationship is also assumed to apply to particle dispersions with solids contents less than 1% by weight, since there is no significant deviation in the viscosity of the aqueous dispersion medium, η = 0.96 mPa s (T = 22 °C). Particle size distributions of fumed or colloidal inorganic particle dispersions are typically measured in plastic cuvettes at solids concentrations of 0.1-1.0%, diluted with dispersion medium or ultrapure water as necessary.
[0036] In the presently claimed invention, the BET surface of the inorganic abrasive particles is determined in accordance with DIN ISO 9277:2010-09.
[0037] For purposes of this claimed invention, an oxidizing agent is defined as a chemical capable of oxidizing the substrate to be polished or one of the layers of that substrate.
[0038] For purposes of this claimed invention, a pH adjuster is defined as a compound added to adjust the pH value to a required value.
[0039] The measurement techniques disclosed herein in connection with the claimed invention are well known to those skilled in the art and therefore are not intended to be limitations of the claimed invention.
[0040] In one aspect of the presently claimed invention, there is provided a tungsten inhibition composition comprising: (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium and benzethonium salts, and (C) Aqueous medium Including, A composition is provided, wherein the pH of the composition is in the range of 5.0 to 11.0.
[0041] The composition comprises components (A), (B) and (C), as well as additional components described below.
[0042] In one embodiment of the claimed invention, the at least one inorganic abrasive particle (A) is selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica.
[0043] In the invention described in the claims, the chemical nature of the at least one inorganic abrasive particle (A) is not particularly limited. The at least one inorganic abrasive particle (A) may have the same chemical nature, or may be a mixture of particles with different chemical natures. In the invention described in the claims, inorganic abrasive particles (A) having the same chemical nature are preferred. The inorganic abrasive particles (A) are selected from the group consisting of metal oxides, metal nitrides, metal carbides, metalloids, metalloid oxides or carbides, silicides, borides, ceramics, diamonds, organic / inorganic hybrid particles, silica, and any mixture of inorganic particles.
[0044] For the purposes of the present claimed invention, the at least one inorganic abrasive particle (A) is One type of colloidal inorganic particles, One type of fumed inorganic particles, Mixtures of different types of colloidal and / or fumed inorganic particles It can be.
[0045] In the invention described in the present claims, the at least one inorganic particle (A) is selected from the group consisting of colloidal or fumed inorganic particles or mixtures thereof. Among these, oxides and carbides of metals or metalloids are preferred. In the invention described in the present claims, the at least one inorganic particle (A) is preferably selected from the group consisting of alumina, ceria, copper oxide, iron oxide, nickel oxide, manganese oxide, silica, silicon nitride, silicon carbide, tin oxide, titania, titanium carbide, tungsten oxide, yttrium oxide, zirconia, or mixtures or composites thereof. In the invention described in the present claims, the at least one inorganic particle (A) is more preferably selected from the group consisting of alumina, ceria, silica, titania, zirconia, or mixtures or composites thereof. In particular, the at least one inorganic abrasive particle (A) is silica. In the invention described in the present claims, the at least one inorganic particle (A) is most preferably colloidal silica particles.
[0046] In another embodiment of the presently claimed invention, the concentration of the at least one type of inorganic abrasive particles (A) is in the range of 0.01% by weight to 10.0% by weight, based on the total weight of the composition.
[0047] In the invention described in the claims, the concentration of the at least one inorganic abrasive particle (A) is 10.0% by weight or less, preferably 5.0% by weight or less, particularly 3.0% by weight or less, for example 2.0% by weight or less, most preferably 1.8% by weight or less, particularly 1.5% by weight or less, based on the total weight of the composition.In the invention described in the claims, the concentration of the at least one inorganic abrasive particle (A) is preferably at least 0.01% by weight, more preferably at least 0.1% by weight, most preferably at least 0.2% by weight, particularly at least 0.3% by weight, based on the total weight of the composition.In the invention described in the claims, the concentration of the at least one inorganic abrasive particle (A) is more preferably in the range of 0.3% by weight to 1.2% by weight, based on the total weight of the composition.
[0048] For the purposes of the claimed invention, the at least one inorganic abrasive particle (A) can be included in the composition with various particle size distributions. The particle size distribution of the at least one inorganic abrasive particle (A) can be unimodal or multimodal. In the case of a multimodal particle size distribution, a bimodal particle size distribution is often preferred. For the purposes of the claimed invention, it is preferred that the particle size distribution of the inorganic abrasive particle (A) is unimodal. However, the particle size distribution of the inorganic abrasive particle (A) is not particularly limited.
[0049] In a preferred embodiment of the presently claimed invention, the average particle diameter of the at least one type of inorganic abrasive particle (A), as determined according to dynamic light scattering, is in the range of 1 nm to 1000 nm.
[0050] The mean or average particle size of the at least one inorganic abrasive particle (A) can vary within a wide range. In the invention described in the claims, the mean particle size of the at least one inorganic abrasive particle (A) is preferably in the range of 1 nm to 1000 nm, preferably in the range of 10 nm to 400 nm, more preferably in the range of 20 nm to 200 nm, and even more preferably in the range of 25 nm to 180 nm. Most preferably in the range of 30 nm to 170 nm, particularly preferably in the range of 40 nm to 160 nm, and most preferably in the range of 45 nm to 150 nm. In either case, the mean or average particle size is measured by dynamic light scattering using an instrument such as a High Performance Particle Sizer (HPPS) manufactured by Malvern Instruments, Ltd. or a Horiba LB550.
[0051] The BET surface of the at least one inorganic abrasive particle (A) can vary within wide limits. For the purposes of the present claimed invention, the BET surface of the at least one inorganic abrasive particle (A) is preferably within 1 m 2 / g or more 500m 2 / g or less, and more preferably 5m 2 / g or more 250m 2 / g or less, and most preferably 10m 2 / g or more 100m 2 / g or less, particularly preferably 20m 2 / g or more 95m 2 / g or less, and most preferably 25m 2 / g or more 92m 2 / g and in each case determined according to DIN ISO 9277:2010-09.
[0052] For the purposes of the claimed invention, the at least one inorganic abrasive particle (A) can be of various shapes. As a result, the shape of the particle (A) may be one or essentially only one type of shape. However, the shape of the particle (A) can also be various. For example, there may be two different shapes of particles (A). For example, (A) can have the shape of an aggregate, a cube, a cube with chamfered edges, an octahedron, an icosahedron, a cocoon, a nodule, a sphere, etc., with or without protrusions or depressions. In the claimed invention, the inorganic abrasive particle (A) is preferably essentially spherical, thereby typically having protrusions or depressions.
[0053] In the invention described in the claims, at least one inorganic abrasive particle (A) is preferably cocoon-shaped. The cocoon may or may not have protrusions or depressions. The cocoon-shaped particles are preferably particles with a minor axis of 10 nm to 200 nm, and preferably with a major axis / minor axis ratio of 1.4 to 2.2, more preferably 1.6 to 2.0. The average shape factor of the particles is preferably 0.7 to 0.97, more preferably 0.77 to 0.92, the average sphericity is preferably 0.4 to 0.9, more preferably 0.5 to 0.7, and the average equivalent circle diameter is preferably 41 nm to 66 nm, more preferably 48 nm to 60 nm (measured by transmission electron microscope and scanning electron microscope in each case).
[0054] In relation to the invention described in the claims, the measurement of the shape factor, sphericity, and circle equivalent diameter of cocoon-shaped particles is described below. The shape factor provides information on the shape and depression of each particle, and can be calculated by the following formula:
[0055] Shape factor = 4π (area / perimeter 2)
[0056] A spherical particle with no dimples has a shape factor of 1. The value of the shape factor decreases as the number of dimples increases. Sphericity gives information about the elongation of individual particles using their moments about the mean value and can be calculated according to the following formula, where M is the centre of gravity of each particle:
[0057] Sphericity = (Mxx-Myy)-[4Mxy2+(Myy-Mxx)2]0.5 / (Mxx-Myy)+[4Mxy2+(Myy-Mxx)2]0.5 Elongation = (1 / sphericity) 0.5
[0058] During the ceremony, Mxx=Σ(xx average) 2 / N Myy=Σ(yy average) 2 / N Mxy=Σ[(xx average)*(yy average)] / N N is the number of pixels forming the image of each particle, x, y are the pixel coordinates, x average is the average of the x coordinates of N pixels forming the image of the particle, The y-mean is the average value of the y-coordinates of the N pixels that form the image of the particle.
[0059] A spherical particle has a sphericity of 1. The sphericity value decreases as the particle becomes elongated. The equivalent circle diameter (ECD) of each non-circular particle provides information about the diameter of a circle that has the same area as the respective non-circular particle. The mean shape factor, mean sphericity and mean ECD are the arithmetic mean of each property relative to the number of particles analyzed.
[0060] In the present claimed invention, the particle shape characterization procedure is as follows: A cocoon-shaped aqueous silica particle dispersion with 20% solids by weight is dispersed on a carbon foil and dried. The dried dispersion is analyzed using Energy Filtered Transmission Electron Microscopy (EF-TEM) (120 kV) and Scanning Electron Microscopy Secondary Electron Imaging (SEM-SE) (5 kV). EF-TEM images with a resolution of 2k, 16 bits, 0.6851 nm / pixel are used for the analysis. After removing noise, the images are thresholded for binarization. The particles are then manually separated. Overlapping and edge particles are discriminated and not used in the analysis. The ECD, shape factor and sphericity as defined above are calculated and statistically classified.
[0061] For the purposes of the invention described in the claims, a representative example of the cocoon-shaped particles may be “FUSO (registered trademark) PL-3” manufactured by Fuso Chemical Co., Ltd., which has an average primary particle size (d1) of 35 nm and an average secondary particle size (d2) of 70 nm, but is not limited thereto. In a more preferred embodiment of the invention described in the present claims, the at least one type of inorganic abrasive particle (A) is a silica particle having an average primary particle size (d1) of 35 nm and an average secondary particle size (d2) of 70 nm.
[0062] In the most preferred embodiment of the invention described in the claims, the at least one type of inorganic abrasive particle (A) is a colloidal silica particle having an average primary particle size (d1) of 35 nm and an average secondary particle size (d2) of 70 nm.
[0063] In another most preferred embodiment of the invention described in the present claims, the at least one inorganic abrasive particle (A) is a cocoon-shaped silica particle having an average primary particle size (d1) of 35 nm and an average secondary particle size (d2) of 70 nm.
[0064] The composition further comprises at least one corrosion inhibitor (B) selected from methylbenzethonium, methylbenzethonium salts, benzethonium and benzethonium salts, the corrosion inhibitor (B) being different from components (A), (C), (D), (E) and (F).
[0065] In one embodiment of the presently claimed invention, the at least one corrosion inhibitor (B) is benzethonium.
[0066] In a preferred embodiment of the presently claimed invention, the benzethonium salt is selected from the group consisting of benzethonium fluoride, benzethonium chloride, benzethonium bromide, benzethonium hydroxide and benzethonium citrate.
[0067] In another preferred embodiment of the presently claimed invention, the methylbenzethonium salt is selected from the group consisting of methylbenzethonium fluoride, methylbenzethonium chloride, methylbenzethonium bromide, methylbenzethonium hydroxide and methylbenzethonium citrate.
[0068] In one embodiment of the claimed invention, the at least one corrosion inhibitor (B) is present in an amount ranging from 0.0001 to 0.009% by weight, based on the total weight of the composition.
[0069] In the present claimed invention, the at least one corrosion inhibitor (B) is preferably present in an amount of 0.009% by weight or less, more preferably 0.08% by weight or less, most preferably 0.07% by weight or less, most preferably 0.06% by weight or less, based on the total weight of the composition. The amount of (B) is preferably at least 0.0001% by weight, more preferably at least 0.0002% by weight, most preferably at least 0.0005% by weight, and particularly preferably at least 0.001% by weight, based on the total weight of the composition. In the present claimed invention, the concentration of the at least one corrosion inhibitor (B) is more preferably in the range of 0.0005% by weight to 0.009% by weight, most preferably in the range of 0.001% by weight to 0.006% by weight, based on the total weight of the composition.
[0070] The composition further comprises an aqueous medium (C). The aqueous medium (C) may be one type or a mixture of different types of aqueous media.
[0071] For the purposes of the claimed invention, the aqueous medium (C) may be a medium containing water. The aqueous medium (C) is preferably a mixture of water and an organic solvent miscible with water. Representative examples of organic solvents include, but are not limited to, C1-C3 alcohols, alkylene glycols, and alkylene glycol derivatives. More preferably, the aqueous medium (C) is water. In one embodiment of the claimed invention, the aqueous medium (C) is deionized water.
[0072] For purposes of the present claimed invention, when the amounts of components other than (C) total y% by weight of the composition, the amount of (C) is (100-y)% by weight of the composition.
[0073] In the presently claimed invention, the amount of aqueous medium (C) in the composition is 99.9% by weight or less, more preferably 99.6% by weight or less, most preferably 99% by weight or less, particularly preferably 98% by weight or less, particularly preferably 97% by weight or less, for example 95% by weight or less, based on the total weight of the composition. In the presently claimed invention, the amount of aqueous medium (C) in the composition is at least 60% by weight, more preferably at least 70% by weight, most preferably at least 80% by weight, particularly preferably at least 85% by weight, particularly preferably at least 90% by weight, for example at least 93% by weight, based on the total weight of the composition.
[0074] The properties of a composition may depend on the pH of the corresponding composition. For the purposes of the claimed invention, the pH value of the composition is preferably 11.0 or less, more preferably 10.5 or less, most preferably 10.0 or less, particularly preferably 9.5 or less, particularly most preferably 9.0 or less. For the purposes of the claimed invention, the pH value of the composition is preferably at least 5.0, more preferably at least 5.5, most preferably at least 6.0. For the purposes of the claimed invention, the pH value of the composition is preferably in the range of 5.0 to 11.0, preferably 5.0 to 10.0, more preferably 5.0 to 9.5, most preferably 5.5 to 9.5, particularly preferably 6.0 to 9.0.
[0075] In one embodiment of the claimed invention, the pH of the composition is in the range of from 5.0 to 10.0.
[0076] In a preferred embodiment of the presently claimed invention, the pH of the composition is in the range of from 6.0 to 9.0.
[0077] The composition further comprises at least one corrosion inhibitor (D), which is different from components (A), (B), (C), (E) and (F).
[0078] In one embodiment of the presently claimed invention, the at least one corrosion inhibitor (D) is selected from polyacrylamides and polyacrylamide copolymers.
[0079] In a preferred embodiment of the claimed invention, the polyacrylamide copolymer is an anionic or non-ionic polyacrylamide copolymer. For the purposes of the claimed invention, the polyacrylamide copolymer is preferably not selected from cationic polyacrylamide copolymers. The use of cationic polyacrylamide copolymers in the composition may lead to aggregation and instability. In a more preferred embodiment of the claimed invention, the polyacrylamide copolymer is a non-ionic polyacrylamide copolymer.
[0080] In a particularly preferred embodiment of the presently claimed invention, the polyacrylamide is a homopolymer of polyacrylamide.
[0081] In one embodiment of the present claimed invention, the at least one corrosion inhibitor (D) is present in an amount ranging from 0.001 to 0.5 wt %, based on the total weight of the composition.
[0082] For the purposes of the claimed invention, the at least one corrosion inhibitor (D) is preferably present in an amount of 0.5% by weight or less, more preferably 0.4% by weight or less, most preferably 0.3% by weight or less, most preferably 0.2% by weight or less, based on the total weight of the composition. The amount of (D) is preferably at least 0.001% by weight, more preferably at least 0.002% by weight, most preferably at least 0.001% by weight, and particularly preferably at least 0.01% by weight, based on the total weight of the composition. For the purposes of the claimed invention, the concentration of the at least one corrosion inhibitor (D) is more preferably in the range of 0.01% by weight to 0.3% by weight, most preferably in the range of 0.01% by weight to 0.2% by weight, based on the total weight of the composition.
[0083] In a preferred embodiment of the claimed invention, the weight average molecular weight of the at least one corrosion inhibitor (D), determined according to gel permeation chromatography, is in the range of 5000 g / mol to 50,000 g / mol. In a more preferred embodiment of the claimed invention, the weight average molecular weight of the at least one corrosion inhibitor (D), determined according to gel permeation chromatography, is in the range of 5000 g / mol to 40,000 g / mol. In a most preferred embodiment of the claimed invention, the weight average molecular weight of the at least one corrosion inhibitor (D), determined according to gel permeation chromatography, is in the range of 7500 g / mol to 15,000 g / mol.
[0084] The composition further comprises at least one oxidizing agent (E), which is different from components (A), (B), (C), (D) and (F).
[0085] In one embodiment of the claimed invention, the at least one oxidizing agent (E) is selected from the group consisting of organic peroxides, inorganic peroxides, nitrates, persulfates, iodates, periodic acid, periodates, permanganates, perchloric acid, perchlorates, bromic acid and bromates.
[0086] In a preferred embodiment of the present invention, the at least one oxidizing agent (E) is selected from the group consisting of peroxides and ferric nitrate, and in a more preferred embodiment of the present invention, the at least one oxidizing agent (E) is hydrogen peroxide.
[0087] In one embodiment of the presently claimed invention, the at least one oxidizing agent (E) is present in an amount ranging from 0.01% to 1.0% by weight, based on the total weight of the composition.
[0088] For purposes of the claimed invention, the concentration of the at least one oxidizing agent (E) is 1.0% by weight or less, more preferably 0.9% by weight or less, more preferably 0.8% by weight or less, and most preferably 0.5% by weight or less, based on the total weight of the composition. For purposes of the claimed invention, the concentration of the at least one oxidizing agent (E) is at least 0.01% by weight, more preferably at least 0.05% by weight, and most preferably at least 0.1% by weight, based on the total weight of the composition.
[0089] For the purposes of the claimed invention, the concentration of hydrogen peroxide as oxidizing agent is preferably from 0.01 to 1.0% by weight, more preferably from 0.05 to 1.0% by weight, most preferably from 0.05 to 0.5% by weight, and particularly preferably from 0.01 to 0.1% by weight, based on the total weight of the composition.
[0090] The compositions of the presently claimed invention may further optionally comprise at least one pH adjuster (F), said at least one pH adjuster (F) being different from components (A), (B), (C), (D), and (E).
[0091] For the purposes of the claimed invention, the at least one pH adjuster (E) is selected from the group consisting of inorganic acids, carboxylic acids, amine bases, alkali hydroxides, ammonium hydroxides, including tetraalkylammonium hydroxides. The at least one pH adjuster (E) is preferably selected from the group consisting of nitric acid, sulfuric acid, phosphorous acid, phosphoric acid, ammonia, sodium hydroxide and potassium hydroxide. In particular, potassium hydroxide is preferred as pH adjuster (E).
[0092] For the presently claimed invention, the amount of said at least one pH adjuster (E) is preferably at most 10% by weight, more preferably at most 2% by weight, most preferably at most 0.5% by weight, in particular at most 0.1% by weight, for example at most 0.05% by weight. For the presently claimed invention, the amount of said at least one pH adjuster (E) is preferably at least 0.0005% by weight, more preferably at least 0.005% by weight, most preferably at least 0.025% by weight, in particular at least 0.1% by weight, for example at least 0.4% by weight, based on the total weight of the composition.
[0093] For purposes of the claimed invention, the composition may optionally include additives. For purposes of the claimed invention, representative examples of additives include, but are not limited to, stabilizers. Additives typically employed in the composition are, for example, those used to stabilize dispersions.
[0094] For purposes of the claimed invention, the concentration of the additive is 10.0% by weight or less, more preferably 1.0% by weight or less, most preferably 0.1% by weight or less, for example 0.01% by weight or less, based on the total weight of the composition. For purposes of the claimed invention, the concentration of the additive is at least 0.0001% by weight, more preferably at least 0.001% by weight, most preferably at least 0.01% by weight, for example at least 0.1% by weight, based on the total weight of the composition.
[0095] A preferred embodiment of the invention as claimed in the present application is (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers A composition comprising: The composition is directed to a pH range of 5.0 or more and 11.0 or less.
[0096] Another preferred embodiment of the invention is (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers A composition comprising: The composition is directed to a pH range of 6.0 or more and 10.0 or less.
[0097] Another preferred embodiment of the invention is (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) aqueous medium; (D) at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers, and (E) at least one oxidizing agent selected from the group consisting of organic peroxides, inorganic peroxides, persulfates, iodates, potassium hydroxide, ferric nitrate, periodic acid, periodates, permanganates, perchloric acid, perchlorates, phosphoric acid, bromic acid, and bromates; A composition comprising: The composition is directed to a pH range of 5.0 or more and 10.0 or less.
[0098] Another preferred embodiment of the invention is (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) aqueous medium; (D) at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers, and (E) at least one oxidizing agent selected from the group consisting of organic peroxides, inorganic peroxides, persulfates, iodates, potassium hydroxide, ferric nitrate, periodic acid, periodates, permanganates, perchloric acid, perchlorates, phosphoric acid, bromic acid, and bromates; A composition comprising: The composition is directed to a pH range of 5.0 or more and 10.0 or less.
[0099] A preferred embodiment of the invention as claimed in the present application is (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts, and (C) Aqueous medium A composition comprising: The pH of the composition is in the range of 5.0 to 10.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0100] A preferred embodiment of the invention as claimed in the present application is (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts, and (C) Aqueous medium A composition comprising: The pH of the composition is in the range of 5.5 to 9.5, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0101] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers A composition comprising: The pH of the composition is in the range of 6.0 to 10.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0102] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers A composition comprising: The pH of the composition is in the range of 6.0 to 9.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0103] Another preferred embodiment of the invention is (A) at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium and benzethonium salts, and (C) Aqueous medium A composition comprising: The composition is directed to a pH range of 6.0 or more and 10.0 or less.
[0104] Another preferred embodiment of the invention is (A) at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) at least one corrosion inhibitor selected from polyacrylamide or copolymers of acrylamide A composition comprising: The composition is directed to a pH range of 6.0 or more and 10.0 or less.
[0105] Another preferred embodiment of the invention is (A) colloidal silica, (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) at least one corrosion inhibitor selected from polyacrylamide or copolymers of acrylamide A composition comprising: The composition is directed to a pH range of 6.0 or more and 10.0 or less.
[0106] Another preferred embodiment of the invention is (A) colloidal silica, (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) aqueous medium; (D) at least one corrosion inhibitor selected from polyacrylamide or copolymers of acrylamide, and (E) at least one oxidizing agent A composition comprising: The composition is directed to a pH range of 6.0 or more and 9.0 or less.
[0107] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 10.0% by mass or less of at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide or acrylamide copolymers A composition comprising: The pH of the composition is in the range of 5.5 to 10.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0108] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 10.0% by mass or less of at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide or acrylamide copolymers A composition comprising: The pH of the composition is in the range of 6.0 to 10.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0109] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 10.0% by mass or less of at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) aqueous medium; (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide or acrylamide copolymers, and (E) at least one oxidizing agent, at least 0.01% by mass to 1.0% by mass A composition comprising: The pH of the composition is in the range of 6.0 to 9.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0110] Another preferred embodiment of the invention is (A) 0.01% by mass or more and 5% by mass or less of at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) aqueous medium; (D) 0.001% by mass or more and 0.3% by mass or less of at least one corrosion inhibitor selected from polyacrylamide or acrylamide copolymers, and (E) at least one oxidizing agent, at least 0.01% by mass to 1.0% by mass A composition comprising: The pH of the composition is in the range of 6.0 to 9.0, The weight percentages in each case are for the composition, based on the total weight of the composition.
[0111] Methods for preparing compositions for inhibiting tungsten etching are generally known. These methods can be applied to the preparation of the compositions of the present claimed invention. The method can be carried out by dispersing or dissolving the above components (A), (B), (D) and (E) in an aqueous medium (C), preferably water, and, if necessary, adjusting the pH value by adding an acid, a base, a buffer or a pH adjuster (F). This method can use conventional and standard mixing methods and mixing devices, such as a stirring vessel, a high shear impeller, an ultrasonic mixer, a homogenizer nozzle or a counterflow mixer.
[0112] One aspect of the presently claimed invention comprises chemically mechanically polishing (CMP) a substrate (S) used in the semiconductor industry in the presence of a composition described herein, wherein the substrate (S) is (i) tungsten and / or (ii) Tungsten alloys The present invention is directed to a method for manufacturing a semiconductor device, comprising:
[0113] The semiconductor device that can be manufactured by the method according to the invention described in the claims is not particularly limited. The semiconductor device can be an electronic component made of semiconductor materials such as silicon, germanium, and III-V materials. The semiconductor device can be manufactured as a single discrete device or as an integrated circuit (IC) consisting of a plurality of devices manufactured on a wafer and connected to each other. The semiconductor device can be a two-terminal element such as a diode, a three-terminal element such as a bipolar transistor, a four-terminal element such as a Hall effect sensor, or a multi-terminal element. The semiconductor device is preferably a multi-terminal element. The multi-terminal element can be a logic device such as an integrated circuit and a microprocessor, or a storage device such as a random access memory (RAM), a read-only memory (ROM), and a phase-change random access memory (PCRAM). The semiconductor device is preferably a multi-terminal logic device. In particular, the semiconductor device is preferably an integrated circuit or a microprocessor.
[0114] Tungsten (W) is commonly used in integrated circuits for copper interconnects. Excess W on the dielectric can be removed by known chemical mechanical polishing processes.
[0115] Generally, the tungsten / tungsten alloy can be produced or obtained in various ways, such as ALD, PVD or CVD process. Generally, the tungsten and / or tungsten alloy can be of any type, form or shape. The tungsten and / or tungsten alloy is preferably in the form of a layer and / or overgrowth. When the tungsten and / or tungsten alloy has the form of a layer and / or overgrowth, the content of the tungsten and / or tungsten alloy is preferably greater than 90%, more preferably greater than 95%, most preferably greater than 98%, particularly greater than 99%, for example greater than 99.9%, based on the mass of the corresponding layer and / or overgrowth. The tungsten and / or tungsten alloy is preferably filled or grown in trenches or plugs between other substrates, and more preferably in trenches or plugs of dielectric materials such as SiO2, silicon, low-k (BD1, BD2) or ultra low-k materials, or other insulating and semiconducting materials used in the semiconductor industry. For example, in Through Silicon Vias (TSV) intermediate processes, isolated materials such as polymers, photoresists and / or polyimides can be used as insulating materials after exposing the TSVs from the backside of the wafer for their insulating / isolation properties during subsequent processing steps of wet etching and CMP.
[0116] In one embodiment of the presently claimed invention, the static etching rate or static etch rate (SER) of tungsten is less than 30 Å / min. In a preferred embodiment of the presently claimed invention, the static etch rate (SER) of tungsten is less than 28 Å / min. In a more preferred embodiment of the presently claimed invention, the static etch rate (SER) of tungsten is less than 25 Å / min.
[0117] One aspect of the presently claimed invention is directed to the use of the compositions of the presently claimed invention to inhibit the etching of tungsten.
[0118] The compositions according to the presently claimed invention have at least one of the following advantages: (1) The compositions and methods of the presently claimed invention exhibit improved performance in inhibiting etching, particularly inhibiting tungsten etching. (2) The compositions and methods of the presently claimed invention prevent erosion of tungsten during chemical mechanical polishing of tungsten-containing substrates. (3) The compositions of the presently claimed invention provide stable formulations or dispersions that do not undergo phase separation. (4) The method of the present claimed invention is easy to apply and requires as few steps as possible. (5) The compositions and methods of the presently claimed invention do not affect the polishing rate of a substrate during chemical mechanical polishing.
[0119] Embodiment Below, a list of embodiments is provided to further illustrate the present disclosure, without, however, intending to limit the present disclosure to the specific embodiments listed below.
[0120] 1. A tungsten etch inhibiting composition comprising: (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium and benzethonium salts, and (C) Aqueous medium Including, The composition has a pH in the range of 5.0 or more and 11.0 or less.
[0121] 2. The composition of embodiment 1, wherein the at least one inorganic abrasive particle (A) is selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica.
[0122] 3. The composition of embodiment 1, wherein the at least one inorganic abrasive particle (A) has an average particle diameter, as determined according to dynamic light scattering, in the range of 1 nm to 1000 nm.
[0123] 4. The composition of embodiment 1, wherein the at least one type of inorganic abrasive particle (A) is present in a concentration ranging from 0.01% by weight to 10.0% by weight, based on the total weight of the composition.
[0124] 5. The composition of any one of embodiments 1-4, wherein the at least one corrosion inhibitor (B) is benzethonium.
[0125] 6. The composition of any one of embodiments 1-5, wherein the benzethonium salt is selected from the group consisting of benzethonium fluoride, benzethonium chloride, benzethonium bromide, benzethonium hydroxide, and benzethonium citrate.
[0126] 7. The composition of any one of embodiments 1-6, wherein the methylbenzethonium salt is selected from the group consisting of methylbenzethonium fluoride, methylbenzethonium chloride, methylbenzethonium bromide, methylbenzethonium hydroxide, and methylbenzethonium citrate.
[0127] 8. The composition of any one of the preceding embodiments, wherein the at least one corrosion inhibitor (B) is present in a concentration ranging from 0.0001% to 0.009% by weight, based on the total weight of the composition.
[0128] 9. The composition of any one of the preceding embodiments, wherein the aqueous medium (C) is deionized water.
[0129] 10. The composition of any one of embodiments 1 to 9, wherein the pH of the composition is in the range of 5.0 or more and 10.0 or less.
[0130] 11. The composition of any one of the preceding embodiments, wherein the pH of the composition is in the range of 6.0 or more and 9.0 or less.
[0131] 12. The composition according to any one of the preceding embodiments, further comprising at least one corrosion inhibitor (D) selected from polyacrylamides and polyacrylamide copolymers.
[0132] 13. The composition of embodiment 12, wherein the polyacrylamide copolymer is an anionic or nonionic polyacrylamide copolymer.
[0133] 14. The composition of embodiment 12, wherein the polyacrylamide is a homopolymer of polyacrylamide.
[0134] 15. The composition of embodiment 12, wherein the at least one corrosion inhibitor (D) is present in a concentration ranging from 0.001% to 0.5% by weight, based on the total weight of the composition.
[0135] 16. The composition of embodiment 12, wherein the at least one corrosion inhibitor (D) has a weight average molecular weight, determined according to gel permeation chromatography, in the range of 5000 g / mol to 50,000 g / mol.
[0136] 17. The composition according to any one of the preceding embodiments, further comprising at least one oxidizing agent (E) selected from the group consisting of organic peroxides, inorganic peroxides, persulfates, iodates, potassium hydroxide, ferric nitrate, periodic acid, periodates, permanganates, perchloric acid, perchlorates, phosphates, bromates, and bromates.
[0137] 18. The composition of embodiment 17, wherein the at least one oxidizing agent (E) is present in a concentration ranging from 0.01% by weight to 1.0% by weight, based on the total weight of the composition.
[0138] 19. The following: (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts, and (C) Aqueous medium Including, The pH of the composition is in the range of 5.0 to 10.0, The composition of any one of embodiments 1-18, wherein the weight percentage in each case is based on the total weight of the composition.
[0139] 20. The following: (A) 0.01% by mass or more and 10.0% by mass or less of at least one type of inorganic abrasive particle; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide and polyacrylamide copolymers Including, The pH of the composition is in the range of 5.5 to 10.0, The composition of any one of embodiments 1-18, wherein the weight percentage in each case is based on the total weight of the composition.
[0140] 21. The following: (A) at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium and benzethonium salts, and (C) Aqueous medium Including, 19. The composition of any one of embodiments 1 to 18, wherein the pH of the composition is in the range of 5.5 or more and 10.0 or less.
[0141] 22. The following: (A) at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) at least one corrosion inhibitor selected from polyacrylamide or copolymers of acrylamide Including, 19. The composition of any one of embodiments 1 to 18, wherein the pH of the composition is in the range of 5.5 or more and 10.0 or less.
[0142] 23. The following: (A) 0.01% by mass or more and 10.0% by mass or less of at least one inorganic abrasive particle selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica; (B) 0.0001% by mass or more and 0.009% by mass or less of at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts; (C) an aqueous medium, and (D) 0.001% by mass or more and 0.5% by mass or less of at least one corrosion inhibitor selected from polyacrylamide or acrylamide copolymers (D). Including, The pH of the composition is in the range of 5.5 to 10.0, The composition of any one of embodiments 1-18, wherein the weight percentage in each case is based on the total weight of the composition.
[0143] 24. A method for chemically and mechanically polishing a substrate (S) used in the semiconductor industry in the presence of a composition as defined in any one of embodiments 1 to 23, wherein the substrate (S) is (i) tungsten and / or (ii) Tungsten alloys A method for manufacturing a semiconductor device, comprising:
[0144] 25. The method of embodiment 24, wherein the static etch rate (SER) of tungsten is less than 30 Å / min.
[0145] 26. Use of a composition according to any one of embodiments 1 to 23 for inhibiting etching of tungsten.
[0146] While the presently claimed invention has been described above in terms of specific embodiments thereof, certain modifications and equivalents will be apparent to those skilled in the art and are intended to be included within the scope of the claimed invention. EXAMPLES
[0147] The presently claimed invention is described in more detail in the following examples. More specifically, the test methods specified below are part of the general disclosure of this application and are not limited to the specific examples.
[0148] A general procedure for slurry preparation and experimentation is described below.
[0149] component: Silica particles (sold under the trade name Fuso® PL-3, manufactured by Fuso Chemical Co., Ltd.) Benzethonium chloride (available from Sigma Aldrich) Deionized water (available from BASF SE) Polyacrylamide (available from Sigma Aldrich) Hydrogen peroxide (available from BASF SE) Slurry composition: The slurry composition comprises: (A) Inorganic abrasive: Silica particles (B) Corrosion inhibitor: Benzethonium chloride (C) Deionized water (DIW) (D) Corrosion inhibitor: Polyacrylamide (E) Oxidizing agent: Hydrogen peroxide (H2O2) Contains:
[0150] The oxidant (E) (1% H2O2) was added immediately (1–15 min) before the slurry was used for static etching rate (SER) measurements.
[0151] method Preparation procedure of the slurry composition Each component in the slurry composition was thoroughly mixed, and all mixing procedures were performed under stirring. Aqueous stock solutions of each compound (A), (B), (D) and (E) were prepared by dissolving the desired amount of each compound in ultrapure water (UPW). For the stock solutions of each component, potassium hydroxide (KOH) or phosphoric acid (H3PO4) was preferably used to aid dissolution. The pH of the stock solutions was adjusted to .about.pH 10 with KOH and .about.pH 6 with H3PO4. For the stock solution (undiluted solution) of (B), the corresponding additive concentration was a 0.001% by weight benzethonium chloride solution, and for the stock solutions of (D) and (E), the concentration of each additive was 1.0% by weight. For (A), a dispersion provided by the supplier was used, typically with an abrasive concentration of about 20%-30% by weight. The oxidizer (E) was used as a 30% by weight stock solution.
[0152] To prepare 10,000 g of slurry, the required amount of (B) stock solution was placed in a mixing tank or beaker and the pH was adjusted to 6 or 10 by adding KOH at a stirring speed of 350 rpm. A predetermined amount of (D) stock solution was added to reach the desired concentration. The pH of the solution was kept at the desired value of 6 or 10 using KOH. Then the required amount of (A) was added. To adjust the final concentration, (C) was added as the balance water to the required amount of oxidizer stock solution. The pH was adjusted to the desired value with KOH (or H3PO4). The desired amount of oxidizer (0.1 wt%) was added approximately 60 minutes before etching.
[0153] Inorganic particles (A) used in each example The average primary particle diameter (d1) is 35 nm, the average secondary particle diameter (d2) is 70 nm (measured by dynamic light scattering using a Horiba Ltd. device), and the specific surface area is approximately 46 m 2 / g of colloidal cocoon-shaped silica particles (A1) (e.g. Fuso® PL-3) were used.
[0154] Particle shape characterization procedure A cocoon-shaped aqueous silica particle dispersion with 20% solids by weight was dispersed on a carbon foil and dried. The dried dispersion was analyzed using an energy-filtered transmission electron microscope (EF-TEM) (120 kV) and a scanning electron microscope secondary electron image (SEM-SE) (5 kV). For the analysis, EF-TEM images with a resolution of 2k, 16Bit, and 0.6851 nm / pixel were used. After noise removal, the images were binarized using a threshold. The particles were then manually separated. A distinction was made between overlapping particles and edge particles, which were not used in the analysis. The ECD, shape factor, and sphericity, as defined above, were calculated and classified statistically.
[0155] A2 has an average primary particle diameter (d1) of 35 nm, an average secondary particle diameter (d2) of 75 nm (measured by dynamic light scattering using a Horiba Ltd. device), and a specific surface area of approximately 90 m 2 / g of agglomerated particles (e.g. Fuso® PL-3H) were used.
[0156] pH Measurement The pH value measurements were performed using a pH combination electrode (Schott, Blue Line 22 pH electrode).
[0157] Static Etch Rate (SER) Experiments SER experiments were carried out as follows. A 2.5 x 2.5 cm piece of PVD tungsten (W) was cut and washed with deionized water (DIW). Each test coupon was treated with 0.1% citric acid solution for 4 minutes and then washed with DIW. The thickness of tungsten (W) (d before) was measured using a four-point probe. · 300ml of freshly prepared slurry with the required hydrogen peroxide concentration was placed in a beaker and heated to 60°C. A tungsten (W) specimen was placed in the slurry and kept in the slurry for 10 minutes in the SER apparatus. The tungsten (W) specimen was removed, washed with DIW for 1 min, and then dried with nitrogen. The tungsten (W) film thickness (after d) was measured again using the same equipment. The static etch rate (SER) was calculated using the following formula:
[0158] SER(A / min)=(before d-after d) / 10
[0159] [Table 1]
[0160] Discussion of the results Table 1 shows the static etching rates, or static etch rates (SER), of various slurry compositions. The addition of benzethonium chloride as a corrosion inhibitor (B) to the slurries results in a SER of tungsten of 30 Å / min or less in the provided pH ranges, compared to slurries without benzethonium chloride as a corrosion inhibitor (B) (Examples 1, 2, 3, and 4). The effect of the benzethonium chloride concentration in the slurry on the SER is shown in Table 1. When the benzethonium chloride concentration was 0.01 mass% or more, the formulation became unstable. Table 1 also shows that the effect of pH on the SER of tungsten is large. In the pH range of 5 to 11, the static etch rate of tungsten (W) was confirmed to be low, and especially at pH 6 or higher, as shown in Table 1.
[0161] Each of the example compositions according to the claimed invention exhibits improved performance with reduced tungsten etch behavior and increased dispersion stability.
Claims
1. A tungsten etching inhibiting composition comprising: (A) at least one inorganic abrasive particle; (B) at least one corrosion inhibitor selected from methylbenzethonium, methylbenzethonium salts, benzethonium, and benzethonium salts, and (C) Aqueous medium Including, The pH of the composition is in the range of 5.0 to 11.0, The at least one corrosion inhibitor (B) is present in a concentration ranging from 0.0001 to 0.009 weight percent, based on the total weight of the composition. A composition comprising:
2. 2. The composition of claim 1, wherein the at least one inorganic abrasive particle (A) is selected from the group consisting of metal oxides, metal nitrides, metal carbides, silicides, borides, ceramics, diamond, organic hybrid particles, inorganic hybrid particles, and silica.
3. 2. The composition of claim 1, wherein the at least one type of inorganic abrasive particle (A) has an average particle diameter, as determined according to dynamic light scattering, in the range of 1 nm to 1000 nm.
4. The composition according to any one of claims 1 to 3, wherein said at least one corrosion inhibitor (B) is benzethonium.
5. The composition of any one of claims 1 to 3, wherein the benzethonium salt is selected from the group consisting of benzethonium fluoride, benzethonium chloride, benzethonium bromide, benzethonium hydroxide and benzethonium citrate.
6. The composition according to any one of claims 1 to 5, wherein the aqueous medium (C) is deionized water.
7. The composition according to any one of claims 1 to 6, wherein the pH of the composition is in the range of 5 or more and 10 or less.
8. The composition according to any one of claims 1 to 7, further comprising at least one corrosion inhibitor (D) selected from polyacrylamides and polyacrylamide copolymers.
9. 9. The composition of claim 8, wherein the at least one corrosion inhibitor (D) is present in a concentration in the range of from 0.001 to 0.5 wt. %, based on the total weight of the composition.
10. 10. The composition according to any one of claims 1 to 9, further comprising at least one oxidizing agent (E) selected from the group consisting of organic peroxides, inorganic peroxides, persulfates, iodates, potassium hydroxide, ferric nitrate, periodic acid, periodates, permanganates, perchloric acid, perchlorates, phosphates, bromic acid and bromates.
11. 11. The composition of claim 10, wherein the at least one oxidizing agent (E) is present at a concentration in the range of 0.01% to 1.0% by weight, based on the total weight of the composition.
12. The method comprises chemically and mechanically polishing a substrate (S) used in the semiconductor industry in the presence of a composition as defined in any one of claims 1 to 11, wherein the substrate (S) is (i) tungsten and / or (ii) Tungsten alloy 2. A method for manufacturing a semiconductor device comprising the steps of:
13. 13. The method of claim 12, wherein the static etch rate (SER) of tungsten is less than 30 Å / min.
14. Use of a composition according to any one of claims 1 to 11 for inhibiting the etching of tungsten.
Citation Information
Patent Citations
Polishing liquid for metal, and polishing method
JP2008251677A
Polishing liquid composition
JP2008277735A
Polishing liquid for CMP, and method of polishing base using the same
JP2008300401A
Compositions and methods for selectively etching titanium nitride
JP2015506583A
Metal compound chemically anchored colloidal particles, methods of production thereof and use thereof
JP2016196632A